Elevated cardiac vagal tone in hypoestrogenic active premenopausal women with functional hypothalamic amenorrhea - Emma ODonnell; Jack M. Goodman; Beverley L. Morris; John S. Floras; Paula J. Harvey (2015)
Elevated cardiac vagal tone in hypoestrogenic active premenopausal women with functional hypothalamic amenorrhea